Analisis Dampak Platform Peer-To-Peer Airbnb Terhadap Usaha Perhotelan Konvensional di Provinsi Bali - Ganapati, I Dewa Gede; Sukwika, Tatan; Sulistyadi, Yohanes (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2021)
The sharing economy platforms in the accommodation, such as Airbnb, gain more public attention. Several hoteliers in Indonesia have complained about the unequal playing of the field due to the alleged tax violations. Some studies on the impact of Airbnb have been discussed in various countries, but this subject has not been widely conducted in Indonesia. This study aims to determine the impact of Airbnb on the conventional hotel industry in Bali and how the conventional hotel’s response to compete with Airbnb. This research was conducted using qualitative research. Data was collected through interviews and secondary data collection. Interviews were conducted with representatives of hoteliers, Airbnb owners, and hospitality associations in Bali. Using forecasting analysis, this study finds that the presence of Airbnb in Bali has an impact on the occupancy rate of conventional hotels in Bali. However, there doesn't a significant impact from Airbnb regarding the hospitality revenue. Meanwhile, conventional hoteliers generally do not make particular efforts to compete with Airbnb. This research implies for the managerial side of hotels and public programs and policies, especially for the Government of Bali in the future to pay attention to consumer protection to provide equal action between conventional hotel and Airbnb owners.